Pendampingan Komunitas Belajar Guru SMP Sektor Sukaraja Dalam Pemanfaatan Teknologi Digital - Diah Selviani; Suwarni Suwarni; Dewi Suranti; Ridho Rahman Kurnianto; Monica Indah Lestari; Fallela Rohma Saputra (Indonesian Journal Publisher, 2025)
The success of curriculum implementation depends on the policies implemented and the effectiveness of teachers in carrying out their duties and responsibilities as educators. Teachers have an important role in facilitating and guiding the student learning process at school by utilizing digitalization. The rapid and rapid development of technology provides a lot of room for teachers to continue to improve their competence. The results of observations obtained that the competence of junior high school teachers in the Sukraja sector, especially in the field of digitalization technology, is still not optimal in utilizing learning media in the classroom. The community service program answers this challenge with the aim that junior high school teachers in the Sukaraja sector can maximize their abilities in carrying out their obligations in the learning process so that they can improve student learning outcomes. Mentoring activities are carried out for two months every Saturday by optimizing the role of the Sukaraja sector junior high school teacher learning community. Based on the results of the feedback (Pre-test and Post-test) that have been carried out, it can be concluded that there is an increase in aspects of participant abilities in utilizing technology and using learning media in the learning process in the classroom which is significant from the results of the Pre-test and Post-test reliability analysis with a correlation value reaching 0.961. This also indicates that there is an influence of increasing partner skills related to the mentoring that has been given and based on the results of validation of the resulting learning media products, the quality of the products produced is better.